Abnormal levels of mitochondrial Ca2+ channel proteins in plasma neuron‐derived extracellular vesicles of early schizophrenia. Issue 8 (22nd July 2022) - Goetzl, Edward J.; Srihari, Vinod H.; Mustapic, Maja; Kapogiannis, Dimitrios; Heninger, George R.
Abstract: Structural alterations or quantitative abnormalities of some mitochondrial ion channels and exchangers are associated with altered neuronal functions and increased susceptibility to mental illness. Here we have assessed levels of functionally prominent mitochondrial calcium ion channel proteins in plasma neuron‐derived extracellular vesicles (NDEVs) of living patients with first episodes of psychosis (FP) and matched controls (Cs). NDEVs were enriched with an established method of precipitation and immunoabsorption by anti‐human CD171 neural adhesion protein (L1CAM) antibody and extracted proteins quantified with ELISAs. CD81 exosome marker‐normalized NDEV levels of leucine zipper EF‐hand containing transmembrane 1 protein (LETM1), transient receptor potential cation channel subfamily M, member 4 (TRPM4), and solute carrier family 8 member B1 (SLC24A6) or mitochondrial Na + /Ca 2+ exchanger (NCLX) were significantly lower for FP patients ( n  = 10) than Cs ( n  = 10), whereas NDEV levels of voltage‐dependent L‐type calcium channel subunit α‐1C (CACNA‐1C) were significantly higher for FP patients than Cs. Abnormal structures or mitochondrial levels of LETM1, NCLX, and CACNA‐1C have been linked through analyses of individual proteins, genome‐wide association studies, and whole exome protein‐coding sequence studies to neurodevelopmental disorders, mental retardation, schizophrenia, and major depressive diseases. A greater understanding of the altered calcium homeostasis in schizophrenia, that is attributable to underlying mitochondrial calcium channel abnormalities, will lead to improved diagnosis and treatment.